2005
DOI: 10.1200/jco.2005.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HER2 Status by Fluorescence in Situ Hybridization and Immunohistochemistry to Predict Benefit From Dose Escalation of Adjuvant Doxorubicin-Based Therapy in Node-Positive Breast Cancer Patients

Abstract: FISH is a reliable method to predict clinical outcome following adjuvant doxorubicin-based therapy for stage II breast cancer patients. There is a moderate level of concordance among the three methods (IHC, FISH, PCR). None of the methods is clearly superior. Although IHC-positive/FISH-positive tumors yielded the greatest interaction with dose of therapy in predicting outcome, no combination of assays tested was statistically superior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 22 publications
2
51
1
1
Order By: Relevance
“…For example, retrospective analyses have shown that anthracycline-based adjuvant therapy is superior to non-anthracycline-based adjuvant chemotherapy in patients with HER2 + tumors, [143][144][145][146][147] and that the dose of doxorubicin may be important in the treatment of tumors that are HER2 + . 148 Prospective evidence of the predictive utility of HER2 status in early-stage [149][150][151][152][153][154] and metastatic breast cancer [155][156][157] is available for trastuzumab-containing therapies. Use of DNA microarray technologies to characterize breast cancer has allowed for the development of classification systems based on gene expression profiles.…”
Section: Estimating Risk Of Relapse or Death And Benefits Of Systemicmentioning
confidence: 99%
“…For example, retrospective analyses have shown that anthracycline-based adjuvant therapy is superior to non-anthracycline-based adjuvant chemotherapy in patients with HER2 + tumors, [143][144][145][146][147] and that the dose of doxorubicin may be important in the treatment of tumors that are HER2 + . 148 Prospective evidence of the predictive utility of HER2 status in early-stage [149][150][151][152][153][154] and metastatic breast cancer [155][156][157] is available for trastuzumab-containing therapies. Use of DNA microarray technologies to characterize breast cancer has allowed for the development of classification systems based on gene expression profiles.…”
Section: Estimating Risk Of Relapse or Death And Benefits Of Systemicmentioning
confidence: 99%
“…Recent studies also describe an association of HER2 amplification with benefit from adjuvant doxorubicinbased chemotherapy (Muss et al 1994, Dressler et al 2005 as well as from paclitaxel administered after four cycles of doxorubicin plus cyclophosphamide . The benefit of HER2-positive patients from anthracyclines appears to be exclusive to the subgroup with HER2-amplified tumors, although some data suggest that this may be due to a co-amplification of the topoisomerase IIa gene (Gennari et al 2008).…”
Section: Her2mentioning
confidence: 99%
“…Moreover, it has been suggested that HER2 overexpression or amplification in breast cancer predicts greater sensitivity to anthracycline-containing chemotherapy (Gennari et al, 2008) and resistance to the CMF regimen (Gusterson et al, 1992). HER2 may also identify patients who are likely to benefit from higher doses of adjuvant chemotherapy (Dressler et al, 2005). The predictive value of HER2 expression regarding the response to taxane-based chemotherapy is considered controversial and the results of the studies have been conflicting, so far .…”
mentioning
confidence: 99%